The cinema dreams its rivals : media fantasy films from radio to the Internet - Young, Paul, 1968- (University of Minnesota Press, 2006)
Paul Young looks at the American cinema's imaginative constructions of three electronic mediaradio, television, and the Internetat the times when these media seemed to hold limitless possibilities. The Cinema Dreams Its Rivals demonstrates that Hollywood is marked by the advent of each new medium, but conversely, the identities of the media are themselves changed as Hollywood turns them to its own purposes.